Effects of a broad-spectrum caspase inhibitor, Z-VAD(OMe)-FMK, on viral hemorrhagic septicemia virus (VHSV) infection-mediated apoptosis and viral replication. (April 2016) - Kim, Min Sun; Lee, Ji Ae; Kim, Ki Hong
Abstract: In the development of inactivated or attenuated viral vaccines for cultured fish, viral titers harvested from the cultured cells would be the most important factor for the determination of vaccine's cost effectiveness. In this study, we hypothesized that the lengthening of cell survival time by the inhibition of apoptosis can lead to an increase of the final titer of viral hemorrhagic septicemia virus (VHSV). To test the hypothesis, we investigated the effects of a broad-spectrum caspase inhibitor, Z-VAD(OMe)-FMK, on VHSV infection-mediated apoptosis in Epithelioma papulosum cyprini (EPC) cells and on the VHSV titers. VHSV infection induced the DNA laddering in EPC cells, and the progression of DNA fragmentation was in proportion to the CPE extension. The progression of DNA fragmentation in EPC cells infected with VHSV was clearly inhibited by exposure to Z-VAD(OMe)-FMK, and the inhibition was intensified according to the increase of the inhibitor concentration. These results confirmed the previous reports that the death of host cells by VHSV infection is through apoptosis. Cells infected with a recombinant VHSV, rVHSV-ΔNV-eGFP, that was generated from our previous study by replacement of the NV gene ORF with the enhanced green fluorescent protein (eGFP) gene ORF, showed earlier and more distinct DNA fragmentations compared to the cells infected with wild-type VHSV, suggesting the inhibitory role of the NV protein in VHSV-mediated apoptosis that was previously reported. The final viral titers in the supernatant isolated from Z-VAD(OMe)-FMK treated cells after showing an extensive CPE were significantly higher than the viral titers from cells infected with virus alone, indicating that the delay of apoptosis by Z-VAD(OMe)-FMK extended the survival time of EPC cells, which lengthen the time for VHSV replication in the cells. In conclusion, Z-VAD(OMe)-FMK-mediated inhibition of apoptosis significantly increased the final titers of both wild-type VHSV and rVHSV-ΔNV-eGFP, indicating that apoptosis inhibition can be a way to get higher titers of VHSV. Highlights: Effect of apoptosis inhibition on VHSV titer was investigated. A caspase inhibitor, Z-VAD(OMe)-FMK, inhibited VHSV-mediated apoptosis. The final titers of wild-type VHSV and rVHSV-ΔNV-eGFP were increased by Z-VAD(OMe)-FMK. Apoptosis inhibition can be a way to get higher titers of VHSV.